Management and information technology after digital transformation - Dahlin, Peter; Keller, Christina 1961-; Ekman, Peter 1969-. (Milton Park, Abingdon, Oxon Routledge, 2022)
"With the widespread transformation of information into digital form throughout society - firms and organizations are embracing this development to adopt multiple types of IT to increase internal efficiency and to achieve external visibility and effectiveness - we have now reached a position where there is data in abundance and the challenge is to manage and make use of it fully. This book addresses this new managerial situation, the post-digitalization era, and offers novel perspectives on managing the digital landscape. The topics span how the post-digitalization era has the potential to renew organizations, markets, and society. The chapters of the book are structured in three topical sections but can also be read individually. The chapters are structured to offer insights into the developments that take place at the intersection of the management, information systems and computer science disciplines. It features more than 70 researchers and managers as collaborating authors in 23 thought-provoking chapters. Written for scholars, researchers, students and managers from the management, information systems and computer science disciplines, the book presents a comprehensive and thought-provoking contribution on the challenges of managing organizations and engaging in global markets when tools, systems and data are abundant"--
Preface
Peter Ekman, Peter Dahlin and Christina Keller

Foreword
Fredrik Nilsson and Fredrik Tell

1. Perspectives on Management and Information Technology after Digital Transformation
Peter Ekman, Peter Dahlin and Christina Keller

2. Digital Transformation: Towards a New Perspective for Large Established Organisations in a Digital Age
Alan W. Brown

Part 1 – The transformation of society and markets
3. Managing Digital Servitization: A Service Ecosystem Perspective
David Sörhammar, Bård Tronvoll and Christian Kowalkowski

4. Caught on the platform or jumping onto the digital train: Challenges for industries lagging behind in digitalisation
Peter Ekman, Magnus Berglind and Steven Thompson

5. Digitalisation for Sustainability: Conceptualisation, Implications and Future Research Directions
Elena Anastasiadou, Linda Alkire and Jimmie Röndell

6. Reaching New Heights in the Cloud: The Digital Transformation of the Video Games Industry
Kevin Walther and David Sörhammar

7. Hyper-Taylorism and Third-order Technologies: Making Sense of the Transformation of Work and Management in a Post-digital Era
Christoffer Andersson, Lucia Crevani, Anette Hallin, Caroline Ingvarsson, Chris Ivory, Inti José Lammi, Eva Lindell, Irina Popova and Anna Uhlin

8. Why Space is Not Enough: Service innovation and service delivery in senior housing
Petter Ahlström, Göran Lindahl, Markus Fellesson, Börje Bjelke and Fredrik Nilsson

9. Challenges in Implementing Digital Assistive Technology in Municipal Healthcare
Ann Svensson, Linda Bergkvist, Charlotte Bäccman and Susanne Durst

Part 2 – Managerial and organisational challenges
10. Modern project management: Challenges for the future
Klas Sundberg, Birger Rapp and Christina Keller

11. Managing the Paradoxes of Digital Product Innovation
Fredrik Svahn and Bendik Bygstad

12. When External Reporting Goes Social: New Conditions for Transparency and Accountability?
Cecilia Gullberg

13. Robotic Process Automation and the Accounting Profession’s Extinction Prophecy
Matthias Holmstedt, Fredrik Jeanson and Angelina Sundström

14. Managing Digital Employee-Driven Innovation: The Role of Middle-Level Managers and Ambidextrous Leadership
Izabelle Bäckström and Peter Magnusson

15. Digital Gamification of Organisational Functions and Emergent Management Practices
Edward Gillmore

16. Leveraging Digital Technologies in Enterprise Risk Management
Jason Crawford and Jan Lindvall

Section 3 – Framing digitalisation
17. The End of Business Intelligence and Business Analytics
Matthias Holmstedt and Peter Dahlin

18. ‘Deleted User’: Signalling Digital Disenchantment in the Post-Digital Society
Cristina Ghita, Claes Thorén and Martin Stojanov

19. The Role of Boundary-Spanners in the Post-Digitalised Multinational Corporation
Henrik Dellestrand, Olof Lindahl and Jakob Westergren

20. The Effect of Digital Transformation on Subsidiary Influence in the Multinational Enterprise
Noushan Memar, Ulf Andersson, Peter Dahlin and Peter Ekman

21. Understanding Information System Outsourcing in the Digital Transformation Era: The Business-relationship Triad View
Cecilia Erixon and Peter Thilenius

22. Transforming the Management/Profession Divide: The Use of the Red–Green Matrix in Swedish Schools
Anton Borell, Johan Klaassen, Roland Almqvist and Jan Löwstedt

23. Integrating research in master’s programmes: Developing students’ skills to embrace digitally transformed markets
Todd Drennan, Cecilia Thilenius Lindh and Emilia Rovira Nordman

Index
Includes bibliographical references and index.
Keywords: Management information systems; Technological innovations; Information technology -- Management